Some Comments Regarding the Synthetic (X)over-bar Chart - Machado, Marcela A. G. [UNESP]; Costa, Antonio F. B. [UNESP] (Taylor & Francis Inc, 2014)
The steady-state average run length (ARL) is a function of the in-control probabilities of being in each nonabsorbing state. Davis and Woodall (2002) tabulated values that are significantly smaller than the steady-state ARLs, because they used the out-of-control probabilities. The synthetic chart signals when a second sample point falls beyond the control limits, no matter whether one of them falls above the centerline and the other falls below it. The side-sensitive version of the synthetic chart does not signal when the points beyond the control limits are on opposite sides. With this rule, the chart detects mean changes more quickly.
Keywords: Shewhart chart; Side-sensitive Chart; Steady-state average run length